China's global growth and Latin American exports - Rhys Jenkins (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
China's global expansion has led to concerns amongst other developing country exporters that they will be displaced by Chinese competition in their export markets. The paper develops a new index to measure the extent of the competitive threat which countries face from China, which is then applied to empirical data on US imports from China and 18 Latin American countries. It also presents new estimates of the impact of China on the value of Latin American exports to the US over the past decade, using an extension of constant market share analysis. It finds that, contrary to many previous studies, China has had a significant impact on the exports of a number of Latin American countries and that this has increased since China joined the WTO in 2001.
Keywords: F14; O54; 330; China; Latin America; US; exports; competitiveness; Internationaler Wettbewerb; Export; Lateinamerika; China